The Effect of fuel mixture composition on gasoline engine emissions in urban conditions - Siregar, Zufri Hasrudy; Nasution, Arif Fadillah; Fazri, Muhammad; Refiza, Refiza; Puspita, Riana; Thamrin, Husni; Nasution, Asmara Sari (Jurnal VORTEKS, 2024)
The increasing number of motorized vehicles in urban areas significantly impacts air quality and public health. Gasoline engine emissions, including CO, HC, and NOx, contribute to pollution issues such as volatile organic compounds (VOCs) and secondary organic aerosols (SOAs). Understanding these factors is crucial for developing effective emission control strategies. This study investigates the effect of ethanol-blended gasoline on vehicular emissions, focusing on CO, HC, and NOx. The research aims to optimize fuel mixtures to reduce harmful emissions while considering environmental and health impacts. The study uses a quantitative experimental design, combining laboratory tests with field trials on 10 vehicles under controlled conditions. Results show that ethanol-blended fuels significantly reduced CO emissions, from 2.4 g/km (E0) to 1.5 g/km (E30). A moderate reduction was observed in HC emissions, from 0.55 g/km (E0) to 0.40 g/km (E30). A slight decrease in NOx emissions was noted. Ethanol's oxygen content improves combustion efficiency, reducing CO and HC emissions, but may slightly increase NOx due to combustion temperature changes. This study highlights the potential of ethanol as an environmentally friendly fuel alternative, with further research needed to address NOx-related challenges